Analysis of Islamic Education Program at Taqwa Mosque Durian Village Medan - Pratama, Agus; Qorib, Muhammad (EDUKASIA Jurnal Pendidikan dan Pembelajaran, 2024)
Islamic religious education programs are a form of real activities that are arranged systematically and integrated with the nuances of Islamic education. This study aims to gain a more detailed understanding of Islamic religious education programs at Taqwa Mosque so that it can be used as a reference for the public in designing Islamic education programs that are needed by the ummah in the future. In this study using descriptive qualitative methods with data collection techniques through interviews, observations and documentation studies. Then the data analysis techniques used are data reduction, data presentation and conclusion. The findings in this study are that the Islamic religious education program at Taqwa Mosque Kampung Durian East Medan has five programs including: 1). Routine Study Program of Muhammadiyah Fathers; 2). Routine Study Program of 'Aisyiyah Mothers; 3). The recitation of Tahsin Al-Qur'an for children; 4). Muhammadiyah Youth Routine Study Program; 5). Friday Alms Routine Program. Of all routine Islamic religious education programs, it is carried out with the aim of meeting what Muslims need today in living the challenges of life in the futur.